2017
DOI: 10.1186/s40900-017-0059-x
|View full text |Cite
|
Sign up to set email alerts
|

Working with public contributors to improve the patient experience at the Manchester Clinical Research Facility: an evaluation of the Experience Based Design approach

Abstract: Plain English summaryThe Experience Based Design (EBD) approach involves patients, staff and members of the public working together to improve a service. This paper evaluates the methods that are used to involve patients and members of the public in a project that aimed to improve the patient experience at Manchester Clinical Research Facility (MCRF). The aim was to explore what helps staff and members of the public to work well together.An evaluation questionnaire was used to get feedback from staff and publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Experience-based co-design (EBCD) (hereby referred to as co-design) allows patients, and providers to impose their collaborative insights on the design and development of the tools and services that they are eventually meant to use [ 16 ]. “Happenings become experiences when they are digested, when they are reflected on, related to general patterns and synthesised” [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experience-based co-design (EBCD) (hereby referred to as co-design) allows patients, and providers to impose their collaborative insights on the design and development of the tools and services that they are eventually meant to use [ 16 ]. “Happenings become experiences when they are digested, when they are reflected on, related to general patterns and synthesised” [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the annual planning method capacity building only includes one employee and the coordinator of each Health Center. However, for the successful implementation of a method, it is indicated that all the stakeholders involved in the process to be trained on it (BAYLISS et al, 2017;CAMPOS, 1992;ISHIKAWA, 1986). The evaluation and adjustments phases of the process do not present the same level of detail in activities like others and they are only monitored in terms of whether the planned actions are being executed as scheduled.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies also show that when both end-user groups were engaged together in development discussions, more concrete and realistic solutions can be identi ed [15]. Experience-based co-design (EBCD) (hereby referred to as co-design) allows patients, and providers to impose their collaborative insights on the design and development of the tools and services that they are eventually meant to use [16]. "Happenings become experiences when they are digested, when they are re ected on, related to general patterns and synthesised" [17].…”
Section: Introductionmentioning
confidence: 99%